SPECIES IDENTIFICATION OF CELL CULTURE BY PCR METHODS - Danlybaeva , G.A.; Imanbekova , M.K.; Sekenova , A.E. (Eurasian Journal of Applied Biotechnology, 2014)
The widespread using of cell cultures for scientific and applied research implicates the long-term cell cultivating process. Wherein this cell culture may have a tendency to change the basic characteristics due to as the cultivating conditions and as contamination by extraneous agents. Normally, when working with mammalian cell cultures researchers concerns about the contamination by various microorganisms (bacteria, yeasts, mycoplasma), while the cross-contamination by other types of cell cultures (both intra- and inter-species) may remain unnoticed. Purity and delicate description of the used model, which in many cases serves continuous cell cultures, are an absolute necessary condition for conducting of biomedical scientific researches, is requires their reliable identification. According to data of the International Cell Line Authentication Committee up to 50% of cell cultures used in research, misidentified or cross-contaminated. This fact is significant justification for authentication of cells and cell lines. In this paper presents the results of determining the species identity 6 new diploid strains obtained in Kazakhstan and 5 continuous cell cultures that are in the depository of the National Center for Biotechnology. Was carried out PCR with species-specific primers to various types of mammals. The experiments were carried out to optimize the conditions for PCR with the concentration of MgCl2 and primers, annealing temperature. The studies found that the optimization of the conditions to determine the presence in a sample of 10 cells/ml. Was revealed that the species-specific primers used showed full compliance with the original test cell cultures mammalian species.